Experimental traumatic brain injury results in estrous cycle disruption, neurobehavioral deficits, and impaired GSK3β/β-catenin signaling in female rats - Fortress, Ashley M.; Avcu, Pelin; Wagner, Amy K.; Dixon, C. Edward; Pang, Kevin C.H. (Experimental neurology, 2019)
An estimated 2.8 million traumatic brain injuries (TBI) occur within the United States each year. Approximately 40% of new TBI cases are female, however few studies have investigated the effects of TBI on female subjects. In addition to typical neurobehavioral sequelae observed after TBI, such as poor cognition, impaired behavior, and somatic symptoms, women with TBI report amenorrhea or irregular menstrual cycles suggestive of disruptions in the hypothalamic-pituitary-gonadal (HPG) axis. HPG dysfunction following TBI has been linked to poor functional outcome in men and women, but the mechanisms by which this may occur or relate to behavior has not been fully developed or ascertained. The present study determined if TBI resulted in HPG axis perturbations in young adult female Sprague Dawley rats, and whether TBI was associated with cognitive and sensorimotor deficits. Following lateral fluid percussion injury, injured females spent significantly more time in diestrus compared to sham females, consistent with a persistent low sex-steroid hormone state. Injured females displayed significantly reduced 17β-estradiol (E2) and luteinizing hormone levels. Concomitantly, injured females were impaired in spatial working memory compared to shams. Impaired GSK3β/β-catenin signaling related to synaptic changes was evident one-week post-injury in the hippocampus among injured females compared to sham females, and this impairment paralleled the deficits in spatial working memory. Sensorimotor function, as evidenced by suppression of the acoustic startle response, was chronically impaired even after normal estrous cycling resumed. These data demonstrate that TBI results in estrous cycle impairments, memory dysfunction, and perturbations in GSK3β/β-catenin signaling, suggesting a potential mechanism for HPG-mediated cognitive impairment following TBI. •Mechanism of behavioral deficits following brain injury in females was examined.•Brainstem and hippocampus-dependent behavior was impaired after brain injury.•Brain injury altered estrous cycling and reduced 17ß-estradiol.•GSK3ß/ß-catenin signaling was reduced in the hippocampus following brain injury.